THE EFFECT OF COMIC STRIPS ON STUDENTS’ READING COMPREHENSION OF RECOUNT TEXTS AT THE EIGHTH GRADE OF SMPN 6 SIAK HULU - Apriliana; Marhamah (SOSIOEDUKASI, 2026)
The objective of this inquiry is to ascertain how employing comic strips affects eighth-grade students at SMPN 6 Siak Hulu's ability to comprehend recount texts. Although interpretation of written discourse is essential and forms the basis for helping students succeed academically, students frequently encounter impediments in apprehending English discourses, particularly recount texts. The learning process, which is still dominated by conventional methods, is one of the reasons students have difficulty understanding texts. A quasi-experimental framework employing a non-equivalent control group was implemented in this inquiry. The sample was delineated through purposive selection predicated upon predetermined criteria aligned with the investigational requisites, encompassing 68 participants apportioned into two groups: an experimental and a control class. Data acquisition was derived from pre-assessment and post-assessment outcomes in both groups. Utilizing SPSS 27, an independent t-test was administered for analytical purposes. The empirical findings reveal that the significant coefficient (Sig., two-tailed) is 0.009, which is inferior to the threshold of 0.05 (0.009 < 0.05). This substantiates the repudiation of the null hypothesis (H0) and the corroboration of the alternative hypothesis (Ha). Consequently, it can be posited that the deployment of comic strips exerts a statistically significant enhancement on the eighth-grade learners at SMPN 6 Siak Hulu in their comprehension of recount texts. The incorporation of comic strips within reading pedagogy functions as an innovative and interactive instructional medium to augment students’ interpretation of written discourse proficiency.